Escola do campo em comunidades de fronteiras - Peizini, Angela Maria Leite (2016)
This research is linked to the research line Curriculum Culture and Post-Graduate Program of Teachers Forming in Education, from Universidade Federal do Espírito Santo and it was developed in articulated efforts to the “Grupo de Pesquisa Culturas” (CNPq), “Parcerias e Educação do Campo”. It has its focus on how and which dialogues appear with the different cultures lived by teachers who work on multiple communities, or on two counties, or on the borders of Aracê District, in Domingos Martins – Espírito Santo – Brazil. To show questions about culture and interculturalism, it has to be make deep reflexions about the many cultures implications on “Educação do Campo”, when is studied in the matter of borders. It’s discussed the interlocution between geographic and cultural borders, in the place where the teachers work and its relations between them through dialogue. It covers the geography not included in maps on the communities’ context and schools near the borders, but in the social relations concrete borders. It’s a case study to analyze documents, to watch planning encounters in the school, as well in the classroom, joining groups in ongoing formation, with the achievement of a interview with the teachers and notes when the research is doing. It lies briefly aspects about the Counties which are frontiers and from “Educação do Campo”. It was made dialogues with the authors to discuss key points, like Countryside Education, (CALDART, 2012), border (HEIDEGGER, 2012; FOUCHER, 2009), cultural hybridization (CANCLINI, 2001; 2013), interculturalism (FOERSTE, 2010), dialogue (FREIRE, 1967), social cartography (ALMEIDA, 2008), community (BRANDÃO, 2012). The researches were made with qualitative approach in education (LUDKE e ANDRÉ, 1996; BRANDÃO, 2008; FICHTNER et al, 2012). It’s pointed that the institutional welfare is very important to decide going and coming in the borders. The teacher’s practices (re) meaning in the interaction with the multiple cultural knowing, in the community or just seen, made in the scholarship dynamics and border communities. It can be said that in the researched school context there are some conditions which favors works on interculturalism. Now, it needs deepening studies about relations established on borders and its impacts to the cultures valorization.